2014
DOI: 10.1038/srep06410
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of polyglutamine-expanded ataxin-3 sequesters its specific interacting partners into inclusions: Implication in a loss-of-function pathology

Abstract: Expansion of polyglutamine (polyQ) tract may cause protein misfolding and aggregation that lead to cytotoxicity and neurodegeneration, but the underlying mechanism remains to be elucidated. We applied ataxin-3 (Atx3), a polyQ tract-containing protein, as a model to study sequestration of normal cellular proteins. We found that the aggregates formed by polyQ-expanded Atx3 sequester its interacting partners, such as P97/VCP and ubiquitin conjugates, into the protein inclusions through specific interactions both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(48 citation statements)
references
References 60 publications
0
48
0
Order By: Relevance
“…We discovered, for the first time, that the inclusions or aggregates of polyQ-expanded Atx7 specifically sequester USP22, as in the case of polyQ-expanded Atx3 aggregates, which specifically sequester P97/VCP and ubiquitin conjugates (35). It has also been reported that GCN5 is present in the nuclear inclusions of polyQ-expanded Atx7 in a SCA7 astrocyte model (14).…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…We discovered, for the first time, that the inclusions or aggregates of polyQ-expanded Atx7 specifically sequester USP22, as in the case of polyQ-expanded Atx3 aggregates, which specifically sequester P97/VCP and ubiquitin conjugates (35). It has also been reported that GCN5 is present in the nuclear inclusions of polyQ-expanded Atx7 in a SCA7 astrocyte model (14).…”
Section: Discussionmentioning
confidence: 69%
“…The Generality and Individuality of polyQ Diseases-Our previous work has demonstrated that polyQ-expanded Atx3 specifically sequesters P97/VCP and influences its function in down-regulating neddylation and proposed a hijacking model for the cytotoxicity and neurodegeneration caused by polyQexpanded proteins (35). Here we report that polyQ-expanded Atx7 sequesters USP22 into aggregates or inclusions through a specific interaction that impairs the function of the DUBm in deubiquitinating H2Bub.…”
Section: Specific Interaction Is Vital For the Sequestration Of Usp22 Bymentioning
confidence: 65%
See 2 more Smart Citations
“…We have also revealed that TDP-35 sequesters normal full-length TDP-43 into inclusions in cells, and poly(A)-containing RNAs play a critical role in their association. Thus, we propose that this sequestration mediated by RNA is associated with the TDP-43 proteinopathy and potentially with neurodegeneration, as in the case of the polyQ-expanded proteins that sequester cellular essential interacting partners into inclusions and lead to a loss-of-function pathology [33].…”
Section: Discussionmentioning
confidence: 99%